Identidades sociais em re-vistas : os sujeitos homens e mulheres sob o olhar do discurso publicitário - Grzeszezeszyn, Claudineya Aparecida (2013)
Given the existence of a new social "scenario", where they constitute technological advances, cultural changes and behavior of the subjects, this study turns to the construction of social identity of individuals men and women, by the advertising discourse, under the production conditions of post modernity. During this period, the subjects see themselves in a moment of "instability of identity," in which social functions are no longer well defined. One of the factors that change is the entry of women into the labor market, which caused the "crisis of the patriarchal family," the fall occurring social identities culturally crystallized. The advertising discourse plays a fundamental role in the production and circulation of meanings, which refer to how men and women - are seen by postmodern society. From there, under the theoretical support of Discourse Analysis, proposed by Pecheux (2010a), Orlandi (2007a), (2007b), (2008), etc. and authors alike, we aim to research, investigate how the language of advertising works, to represent the "new" social identities in / post modernity. Therefore, the corpus consists of ten advertisements, selected national magazines, targeted at different audiences and different products or services advertisements. About the media, advertising and post-modern society, and linking them to the creation of social identities in advertisements, mobilized authors as McQuail (2003), Carvalho (1996, 2000), Castells (1999a, 1999b), among others. In the current analysis, we focus on the imaginary formations as production process of advertising discourse, in which the subject-enunciator anticipates the image of himself and his interlocutor, in preparing the speech, promoting the representation and identification of individuals men and women. The effects of meaning are produced from the intersection of the intradiscourse interspeech, showing the materiality discursive (verbal and imagery), the work of the linguage and in it, the inscription of history. Therefore so many times, by the effect of "pre-built", the ideological affiliations return intradiscourse does that refer to the patriarchal society, which "returns" to the subjects postmodern traditional social identities. Finally, we found that there were significant changes with the regard of the construction of social identity of men and women, and are currently represented in a "multifaceted" and "ephemeral" by advertising discourse. Thereby, while it is "registered", also happens to "repetition" of social and cultural identities crystallized, having thus a kind of return to the same, and the already-said.